Heat exchangers made of polymer-bonded La(Fe,Si)(13) - Skokov, K. P.; Karpenkov, D.Yu.; Kuz’min, M.D.; Radulov, I.A.; Gottschall, Tino; Kaeswurm, Barbara; Fries, Max; Gutfleisch, Oliver (Journal of Applied Physics, 2014)
We report on magnetocaloric properties of polymer-bonded La(Fe,Si)(13) heat exchangers with respect to the grain size of the powder used and the pressure applied for compaction of plates. Quite remarkably, it was found that the values of the adiabatic temperature change of polymer-bonded plates are 10% higher than in the initial bulk material. A critical value of the pressure applied during the compaction was found. Exceeding this value leads to a drastic reduction of the magnetocaloric effect due to cracking and comminution of the initial 50-100 mu m grains down to 1-10 mu m fragments. Compacting the LaFe11.6Si1.4 powder with 5 wt.% of silver epoxy under an optimal pressure of 0.1 GPa resulted in the production of 0.6 mm-thick plates. These plates were subsequently stacked and glued together into a simple porous heat exchanger with straight 0.6 mm-width channels. (C) 2014 AIP Publishing LLC.